Control of Redroot (Lachnanthes caroliniana) in Pastures - Jason Ferrell; Brent Sellers; Joseph Walter (EDIS, 2008)
SS-AGR-290, a 2-page illustrated fact sheet by Jason Ferrell, Brent Sellers, and Joseph Walter, describes this wetland plant with red rhizome and flattened leaves which can be a problem in newly established, declining, or mole-cricket damaged pastures. Includes herbicide recommendations. Published by the UF Department of Agronomy, December 2007.